Veados-campeiros (Ozotoceros bezoarticus (Linnaeus, 1758)) (Mammalia : Cervidae) no nordeste do Pantanal do Mato Grosso (RPPN SESC Pantanal), Barão de Melgaço, MT : densidade, tamanho populacional e uso dos hábitats - Manço, Aniela Moretti (2004)
Ozotoceros bezoarticus (pampas deer) is a South American deer associated to open habitats. The species avoids closed formations. The reduction of habitats has drive the speeies to near the extinction threat. The present study aims to estimate the population density, size and habitat preferences in an area located in northeastem of the Pantanal wetland (SESC Pantanal Reserve, Barão de Melgaço, MT). Through six transects sampled by horseback in dry and wet season, stratified and not stratified samples were analyzed using the software DISTANCE, and by Hayne's estimator and Modified Hyne estimatorto evaluate the population density. In the wet season the estimated density was of 0,87 deer/km², and a population size of 31 individuaIs. In the dry season the estimated density 0,27 deer/km², and a popuIation size of 27 individuaIs. In the road stratum the deer density was of 1,19 deer/km². In no-road stratum ihe deer densiiy was of 0,83 deer/km². The number of individuaIs associated to each stratum was 5 and 26, respectively. The most selected habitats in the wet season was “campos de murundus” (earthmound fields) with Brachiaria humidicola grass. In the dry period the most selected habitat was open grasslands. Among all the used habitats the earthmound fieIds were the most avoided in the two seasons. The seasonaI variations (floodings) and changes in the vegetation zones, as result of human activity reduction, may affeet the distribution of the species and the population size moving the species away from optimaI conditions.